Middle class vulnerability to covid-19 pandemic effects and government measures in Metropolitan Lima - Bürkli Bürkli, Hans Adrian; Hernández Garavito, Jorge; Mendoza García, Diego Alberto; Riva Zaferson, Franco Alberto (360: Revista de Ciencias de la Gestión, 2021)
Using National Household Survey data, this study examines the situation of Peruvian middle class households in Metropolitan Lima and Callao prior to the COVID-19 pandemic through financial and non-financial variables in order to identify vulnerability factors in the overall population and in income quintiles. The analysis has revealed that health, income and labor are the most vulnerable indicators and could be heavily affected by government measures against COVID-19, such as mandatory social isolation (lockdown), social distancing, and movement and gathering restrictions. In this context, households in the lowest quintile are substantially more susceptible to falling into poverty due to economic instability, labor informality and lack of social protection. The study results suggest that the definition of “vulnerability” needs to go beyond poverty measurements to improve the focalization of government policies and strategies in similar crises.